Workplace digitalisation and work-nonwork satisfaction: the role of spillover social media. Issue 8 (11th June 2021) - Farivar, Farveh; Richardson, Julia
ABSTRACT: Prior research has shown that the use of Information Communication Technology (ICT) outside work hours blurs work and nonwork boundaries, exacerbates work-life conflict, and negatively impacts employees' satisfaction. Conversely, personal ICT-use at work, or cyberloafing, has become an increasing concern among employers given its putative impact on individual and organisational performance. We use the 'dual-lens' of Boundary theory and Set theory to conceptualise employees' work-related ICT-use outside work hours and cyberloafing as a set-theoretic phenomenon reflecting 'spillover social media'. Drawing on a survey of 403 Australian white-collar employees and using a set-theoretic approach (fsQCA), we discuss the following findings. First, spillover social media positively impacts work satisfaction among people who are single and do not have children. Second, spillover social media positively contributes to nonwork satisfaction among married male participants who do not have children. Third, that parents only reported nonwork satisfaction if they did not engage in spillover social media.